Perjanjian Hudaybiyyah Dalam Prespektif Ralp Dahrendorf - Moh. Khoirul Fatih dan Moh. Sahlul Khuluq (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
This paper seeks to investigate further about how the peace efforts of Muslims through the Hudaybiyah Agreement? What conflict resolution is offered in the agreement? As well as analyzing the hudaybiyah agreement within the framework of Ralph Dahrendorf's conflict resolution theory. The history of Islam shows that "Islam was born" in conditions of conflict, which is very strong at the local and national levels. The presence of Islam on the one hand provides hope for Arab society, on the other hand it poses a threat to the survival of the Qurays tradition that has developed. This led to violent acts of the Quraysh against the Prophet Muhammad and his followers. The Hudaybiyyah Agreement was successfully formed because of the wise attitude shown by the Prophet Muhammad by holding a negotiation process with the enemy, so that there would be no bloody war which would later bring losses to both parties, both the Muslims and the Quraysh of Mecca. As Dahrendorf's theory states that the negotiation stage is considered very important to be used to prevent the outbreak of conflict, in the case of Hudaybiyyah the negotiation stage was used by the Prophet in an effort to reduce the conflict between the Muslims and the Quraysh of Mecca so that it would not escalate. In the context of Islamic civilization, the Hudaybiyyah agreement is a mirror that the superiority of the military and Islamic war armies does not necessarily carry out hegemony. However, it has taken into account the interests of humanity between conflicting peoples. Therefore, in every conflict resolution a peaceful approach is important.